Is the Double Dose Alpha-Blocker Treatment Superior Than the Single Dose in the Management Of Patients Suffering From Acute Urinary Retention Caused By Benign Prostatic Hyperplasia? - Kara, Önder; Yazici, Merve (Urology Journal, 2014)
Abstract Purpose: To compare the efficacy and safety of single (tamsulosin) and double dose (tamsulosin + alfuzosin) alpha-blocker therapy for treating catheterized patients with acute urinary retention (AUR) due to benign prostatic hyperplasia (BPH). Materials and Methods: Seventy patients with AUR due to BPH were catheterized and randomized into two groups: the single dose group (0.4 mg tamsulosin, 35 patients) and the double dose group (0.4 mg tamsulosin + 10 mg alfuzosin, 35 patients). The catheter was removed after 3 days, and the patients were put on trial without catheter (TWOC). Results: Seventy males (mean age, 71.2 years) were randomly assigned to receive double or single dose alpha-blocker (35 patients per group). The intent-to-treat population consisted of 70 males. Twenty-seven individuals in the double dose group and 19 in the single dose group did not require re-catheterization on the day of the TWOC (77% and 54%, respectively; P = .003). Success using free-flow variables was also higher in the males who received double dose alpha-blocker compared with single dose therapy (48% vs. 40%; P = .017). Conclusion: TWOC was more successful in males treated with double dose alpha-blockers, and the subsequent need for re-catheterization was also reduced. The side-effect profiles were similar in the single and double dose alpha-blocker groups and were consistent with the known pharmacology. These results state that double dose alpha-blocker treatment can be recommended for treating males after catheterization for AUR, which may reduce the need for re-catheterization.